2022
DOI: 10.1111/bjhp.12591
|View full text |Cite
|
Sign up to set email alerts
|

“We want to live a little longer and our family want[s] us around”: A summative content analysis of adherence to COVID‐19‐related guidelines using the Theoretical Domains Framework

Abstract: Objective Public adherence to COVID‐19‐related government guidance varied during the initial lockdown in the UK, but the determinants of public adherence to such guidance are unclear. We capture spontaneous reflections on adherence to UK government guidance from a representative UK sample, and use the TDF to identify key determinants of COVID‐related behaviours. Design The design was cross‐sectional. Methods Qualitative data were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(23 citation statements)
references
References 91 publications
0
23
0
Order By: Relevance
“…Overall adherence was generally high. Eight studies [27][28][29]33,[36][37][38][39] reported high adherence among participants, with a further two studies [30,31] reporting moderately high adherence. Three studies didn't provide data on levels of adherence per se, only factors related to adherence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall adherence was generally high. Eight studies [27][28][29]33,[36][37][38][39] reported high adherence among participants, with a further two studies [30,31] reporting moderately high adherence. Three studies didn't provide data on levels of adherence per se, only factors related to adherence.…”
Section: Resultsmentioning
confidence: 99%
“…sound evidence for a non-randomized study but not comparable to an RCT [24]). Among the qualitative studies, all seven studies [32][33][34][35][36][37][38] were deemed high-quality qualitative studies according to CASP criteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…"I try to stay 2 m away from everyone however this is not always possible in a small shop and most customers do not care about social distancing." (Leather et al, 2022) Comfort as a driver for behaviour (n = 45). Comfort, enjoyment, and convenience were drivers for behaviour change within the smoke-free and COVID-19 literature.…”
Section: Physical Environmentbarriers Dictate Behavioursmentioning
confidence: 99%